Peran Non-Governmental Organization (NGO) dalam Pemenuhan Hak Pendidikan Formal Bagi Anak Pengungsi Luar Negeri di Provinsi DKI Jakarta - Hidayah, Nikmatul (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2024)
This research discusses the role of Non-Governmental Organizations (NGOs) in fulfilling the right to formal education for refugee children in the DKI Jakarta province. This research is qualitative-descriptive research with primary data sources are interviews and field observations and secondary data are from books, journals and mass media. In answering research questions, researcher use the concept of the role of NGOs. NGOs have roles as implementers, catalysts and partners. The results of this research explain that Dompet Dhuafa as NGO in DKI Jakarta, has a role as a partner of the sub-national government of DKI Jakarta and also UNHCR. Dompet Dhuafa through the School for Refugees (SfR) provides preparatory education before refugee children enter formal school by providing Indonesian language education as well as literacy and arithmetic. This preparatory class helps refugee children understand the teacher's explanations during the classroom learning process. Keyword : NGO, formal education, refugee children ABSTRAKPenilitian ini membahas tentang peran Non-Governmental Organization (NGO) dalam pemenuhan hak untuk mendapatkan pendidikan formal bagi anak pengungsi luar negeri di provinsi DKI Jakarta. Penilitian ini adalah penilitian kualitatif-deskriptif dengan sumber data primer yaitu wawancara dan observasi lapangan dan data skunder yaitu berasal dari buku, jurnal dan media massa. Dalam menjawab pertanyaan penelitian, peneliti menggunakan konsep peranan NGO. NGO mempunyai beberapa peranan yaitu sebagai implementor, catalyst, dan patner. Adapun hasil penelitian ini menjelaskan bahwa NGO di DKI Jakarta yaitu Dompet Dhuafa memiliki peran sebagai patner atau mitra dari pemerintah sub-nasional yaitu pemerintah provinsi DKI Jakarta dan juga Lembaga PBB untuk pengungsi yaitu UNHCR. Dompet Dhuafa melalui School for Refugee menyediakan Pendidikan persiapan sebelum anak pengungsi masuk sekolah formal yaitu Pendidikan Bahasa Indonesia dan juga baca tulis dan berhitung. Kelas persiapan ini sangat membantu anak-anak pengungsi memahami keterangan guru ketika proses pembelajaran diskelas.